Genome Sequence Resource of Serratia ureilytica HNU47 A Strain with Biocontrol Potential Against Bacterial Wilt Pathogen Ralstonia solanacearum - Cao, Xiulan (Plant disease, 2023)
Serratia ureilytica HNU47 was originally isolated from rhizosphere soil of stock in a continuous cropping tomato-planting field, which has excellent antagonistic ability against Ralstonia solanacearum. Here, we sequenced the genome of HNU47 to gain insights into the underlying basis of its antagonistic activity. Results of phylogenetic analysis of the whole genomic sequence demonstrated that HNU47 belongs to S. ureilytica. Through antiSMASH analysis, 10 secondary metabolite biosynthesis gene clusters were predicted. There were only two gene clusters with similarity higher than 95% with known compounds' gene clusters and the similarities of the other eight gene clusters were lower than 30%, including three gene clusters with no homology. In addition, biocontrol experiments confirmed that HNU47 could decrease the incidence of bacterial wilt caused by R. solanacearum on tomato. These findings support the potential of developing S. ureilytica HNU47 as a biocontrol agent against R. solanacearum by producing some unknown active compounds. The genome sequence reported here is also useful for revealing the modulation mechanisms underlying biosynthesis of active compounds